Síntese, caracterização e avaliação cinética de vasodilatação com complexos metálicos doadores de óxido nítrico - Paz, Iury Araújo (2019)
Coordination compounds containing the 5-azaindole (5-aza), the bidentate 2,2'-bipyridine (bpy) and 1,10 -phenanthroline (phen) ligands were synthetized and characterized by spectroscopic and electrochemical techniques. The nitrosyl complexes cis-[Ru(NO)(5-aza)(L)2](PF6)3.H2O, where L = bpy or phen, showed characteristic signals of stretching frequency of the nitrosyl group at 1942 cm-1 in both complexes, suggesting the coordination of the NO+ group to the metal center via nitrogen atom . In the UV-vis spectrum, there are absorption bands of type intraligand (IL) and metal to ligand g=charge transfer (MLCT), including the nitrosyl group. Through the hydrogen nuclear magnetic resonance technique, it was possible to observe the presence of 22 hydrogens, confirming part of the proposed structures. The cyclic voltammogram showed waves around 185 V vs Ag / AgCl, consistent with the reduction of the nitrosyl - {RuNO}6/7 group. Elemental analysis data suggest a hydration water molecule in the solid composition. Both complexes release NO under visible light irradiation and react to glutathione (GSH). The studied complexes exhibit nitroysl-nitrite interconvertion pK in the range pH 2 and 3, similar to most analogous complexes. The complexes presented interesting biological vasodilation properties: result in Wistar rat aortic ring dilation, dependent on the heme group. The complex with bpy ligand showed no dependence on eNOS enzyme, and the complex with phen ligand partially demonstrated dependence on this enzyme, resulting in a synergistic effect. The complexes showed no statistical differences in potency in vasodilation, however, the phenanthroline complex was shown to have slower vasodilation kinetics than bipyridine. A comparison with analogous complexes demonstrated an auxiliary ligand dependence on vasodilation kinetics effects.